Charlie Davis’ Psychological Conflicts and Their Resolution in Girl in Pieces - Maratus Solichah, Puja Ananda (Journal of Literature, Linguistics, & Cultural Studies, 2024)
Conflict has an important role in human life. At a certain level, conflict is needed as a means of human change as a member of society or personally so that they become better. This research is important and interesting to carry out because in everyday life there is always conflict, whether from within ourselves or from others. Conflict that is well managed can foster creativity, innovation in problem solving, and become a driving force in social dynamics or personal and change. In the Girl in Pieces by Kathleen Glasgow, a lot of conflicts occur to the main character, Charlie Davis, because she experienced a difficult and dark life to recovery from NSSI (Non-Suicidal Self Injury) suffered. This study aims to represent the types of conflicts suffered by the main character and how she overcomes it. This study uses the literary criticism with the novel as the object of this study. This study applies the psychological approach and the conflict theory proposed by Kurt Lewin (1935) that discussed the types of conflict and the resolution of it. The result of the study revealed that Charlie experience two type of conflict, avoidance-avoidance conflict and approach-avoidance conflict. Another result found is Charlie overcome her conflict with all the types of valence, positive valence where she achieve her goal and it gave her positive value, and negative valence that gave her negative impact.